Multisector Dynamics: Advancing the Science of Complex Adaptive Human‐Earth Systems. Issue 3 (2nd March 2022) - Reed, Patrick M.; Hadjimichael, Antonia; Moss, Richard H.; Brelsford, Christa; Burleyson, Casey D.; Cohen, Stuart; Dyreson, Ana; Gold, David F.; Gupta, Rohini S.; Keller, Klaus; Konar, Megan; Monier, Erwan; et al.
Abstract: The field of MultiSector Dynamics (MSD) explores the dynamics and co‐evolutionary pathways of human and Earth systems with a focus on critical goods, services, and amenities delivered to people through interdependent sectors. This commentary lays out core definitions and concepts, identifies MSD science questions in the context of the current state of knowledge, and describes ongoing activities to expand capacities for open science, leverage revolutions in data and computing, and grow and diversify the MSD workforce. Central to our vision is the ambition of advancing the next generation of complex adaptive human‐Earth systems science to better address interconnected risks, increase resilience, and improve sustainability. This will require convergent research and the integration of ideas and methods from multiple disciplines. Understanding the tradeoffs, synergies, and complexities that exist in coupled human‐Earth systems is particularly important in the context of energy transitions and increased future shocks. Key Points: Sustainability, climate change, and energy transitions are highly interdependent challenges MultiSector Dynamics (MSD) studies these challenges through the lens of complex, adaptive human‐Earth systems Confronting human‐Earth systems complexity requires a diverse, transdisciplinary workforce and community‐level open science